68.9k views
21 votes
Rewrite! Write an new and equivalent equation that is easier to solve

Rewrite! Write an new and equivalent equation that is easier to solve-example-1
User Achwilko
by
4.8k points

2 Answers

8 votes


\sf{ 7( √(m+1) - 3)=21}


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{√(m+1) - 3)=(21)/(7)}


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{ 7( √(m+1) - 3)=3}


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{√(m+1) =6}


\: \: \: \: \: \: \: \: \: \: \: \:

Get the power of 2 in both sides.


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{( √(m + 1))^2 = 6^2}


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{m+1=36}


\: \: \: \: \: \: \: \: \: \: \: \:


\sf{m=35}


\: \: \: \: \: \: \: \: \: \: \: \:

So the answer is m = 35

User Ariel Kabov
by
4.3k points
10 votes


{\huge{\fcolorbox{yellow}{red}{\orange{\boxed{\boxed{\boxed{\boxed{\underbrace{\overbrace{\mathfrak{\pink{\fcolorbox{green}{blue}{Answer}}}}}}}}}}}}}


\sf 7( √(m + 1) - 3) = 21

we will multiply 7 with bracket


\sf 7 √(m + 1) - 21 = 21

Now we will take (-21) on LHS to RHS


\sf 7 √(m + 1) = 21 + 21 \\ \\ \sf7 √(m + 1 ) = 42 \\ \\ \sf √(m + 1) = (42)/(7) \\ \\ \sf √(m + 1) = 6

Now we will do squaring both sides


\sf {( √(m + 1)) }^(2) = {(6)}^(2) \\ \\ \sf \red {m + 1 = 36}

User Steve Melnikoff
by
5.1k points